The Degree of Practicing Innovative Leadership by Female Principals of Public Secondary Schools in Amman and its Relation to their Job Performance - Magableh, Atef Y.; Jaradat, Maram M.; Al kilani, Lubna T. (Opción)
This study aimed at finding out the degree of practicing innovative leadership by female principals of public secondary schools in Amman and its relation to their job performance. The random sample of the study consisted of (375) female teachers. The results showed that the degree of practicing innovative leadership by public secondary school female principals in Amman was medium with a mean of (3.54) .The level of job performance of public secondary school female principals in Amman medium. The mean was (3.26) and there was a positive significant correlational relationship between innovative leadership and job performance of principals.